INSTITUSIONALISASI NILAI-NILAI SOSIAL BUDAYA MASYARAKAT TENGGER DI TENGAH KEPUNGAN AGAMA-AGAMA - Ulum, Bahrul; Mufarrohah (LPPI Universitas Al-Qolam Malang, 2017)
The people of Tengger are known as a strong society in upholding the essential values of the sublime as the inheritance of the ancestors. The development of the tourism industry (especially Mount Bromo Peak), does not affect the Tengger community in implementing the socio-cultural values that exist. This persistency is seemly caused by the process of institutionalization of the values in this unique community. The institutionalization process of socio-cultural values in Tengger society is inseparable from the role of socialization of the socio-cultural values itself, both from government leaders, adat leaders, and family leaders. The process of institutionalizing values to society passes through several stages including the